Study on the protective effect of naringin-regulated lncRNA GAS5 against mitochondrial apoptosis in osteoarthritic chondrocytes - LIN Qin; ZHU Yingkai; LIN Yanming; LAN Shujie; CHEN Changxing; FU Changlong (康复学报)
ObjectiveTo investigate the protective effect of naringin on mitochondrial apoptosis in osteoarthritic (OA) chondrocytes by regulating lncRNA GAS5.MethodsIn vivo experiments, a rat OA model was constructed using the modified Hulth method and treated with naringin at 70 mg/kg by gavage for 8 weeks. Magnetic resonance imaging and ultrasound were used to identify the success of modeling; histopathological changes in rat articular cartilage were assessed using toluidine blue and saffron O staining; changes in the levels of lncRNA GAS5 in rat cartilage tissues after naringin intervention were detected by Real-time PCR; Western blot detected Caspase-3, Bax, MMP-13 and Cyt-C in rat cartilage tissues. In vitro experiments, Lenti-lncRNA GAS5 was used to infect sodium nitroprusside (SNP)-induced chondrocytes, and the expression of lncRNA GAS5 was detected by fluorescence in situ hybridization in rat chondrocytes; after silencing of lncRNA GAS5, the expression level of lncRNA GAS5 in rat chondrocytes was detected by Real-time PCR; Western blot detected the protein levels of Caspase-3, Bax, MMP-13 and Cyt-C.Results① Pathological changes of cartilage tissue: The articular cartilage matrix in naringenin group was relatively complete, the surface was relatively smooth, the structure was clear, the tide line was more complete, the number of chondrocytes was more full, the arrangement was more orderly, the cartilage staining was more uniform, and the structure was significantly restored than that in the model group. ② lncRNA GAS5 expression in cartilage tissue: Compared with model group, lncRNA GAS5 expression in naringin group was decreased (P<0.01). ③ Expression of proteins related to mitochondrial apoptosis in cartilage tissues: Compared with model group, the expressions of Caspase-3, Bax, MMP-13 and Cyt-C in cartilage tissues of naringin group were decreased (P<0.01). ④ Fluorescence expression of lncRNA GAS5 in chondrocytes: FISH results showed that the fluorescence expression of lncRNA GAS5 was decreased after naringin treatment of SNP-induced chondrocytes (P<0.01). ⑤ The protein expressions of Caspase-3, Bax, MMP-13 and Cyt-C in chondrocytes: Compared with the model group, the protein expressions of Caspase-3, Bax, MMP-13 and Cyt-C in naringin group were significantly decreased (P< 0.01). In addition, silencing lncRNA GAS5 will weaken the therapeutic effect of naringin on OA.ConclusionNaringin inhibits chondrocyte mitochondrial apoptosis and protects degraded cartilage tissues by down-regulating the expression of lncRNA GAS5, which has therapeutic value for OA diseases.